Erratum: Cheng, Z.Y., et al. Casticin Induces DNA Damage and Affects DNA Repair Associated Protein Expression in Human Lung Cancer A549 Cells (Running Title: Casticin Induces DNA Damage in Lung Cancer Cells). Molecules 2020, 25, 341 - Editorial Office, Molecules (Molecules (Basel, Switzerland), 2021)
We wish to report an error in the title of article [...]